2012
DOI: 10.1088/1748-0221/7/01/c01010
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of direct-conversion x-ray detection using cadmium zinc telluride films

Abstract: Polycrystalline Cd(Zn)Te films deposited by vacuum thermal evaporation are investigated as a direct-conversion medium for x-ray detection. The use of evaporation techniques allows for the preparation of large-area films with the potential for large-area x-ray imaging with high spatial resolution. Films with compositions of Cd 1−x Zn x Te (x = 0.15, 0.25, 0.3) were prepared to a thickness of 20 µm on slide glass substrates with an aluminum or indium tin oxide (ITO) bottom electrode and a silver top electrode, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In order to obtain low cost and large-area uniform Cd 1 À x Zn x Te for X-ray imaging detectors [7] it is necessary to use films with the thickness of 30 mm [8,9] and higher instead of bulk crystals. Furthermore, since Cd 1 À x Zn x Te have p-type conductivity, they may be used as alternative top adsorber layers in solar cells with the optimal band gap about of (1.7-1.8) eV at x E0.30 for effective conversion of light absorption into electrical power.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain low cost and large-area uniform Cd 1 À x Zn x Te for X-ray imaging detectors [7] it is necessary to use films with the thickness of 30 mm [8,9] and higher instead of bulk crystals. Furthermore, since Cd 1 À x Zn x Te have p-type conductivity, they may be used as alternative top adsorber layers in solar cells with the optimal band gap about of (1.7-1.8) eV at x E0.30 for effective conversion of light absorption into electrical power.…”
Section: Introductionmentioning
confidence: 99%
“…This imaging modality needs photoconductors that have a higher atomic number (Z). Higher Z semiconductors such as CdTe, CdZnTe, HgI 2 , PbI 2 , PbO have shown good potential for applications in direct conversion imaging with favorable electrical properties; see, for example, references [16][17][18][19][20][21][22][23][24] for a selection of potential high-Z semiconductors, some of which were reported in this journal.…”
Section: Introduction and Perspectivesmentioning
confidence: 99%
“…Kang et al deposited polycrystalline Cd 1 À x Zn x Te films by vacuum evaporation to investigate its property as a transducer for x-ray detection. Experiments revealed that multilayered Cd 1 À x Zn x Te structures, along with charge-blocking layers, are suitable transduction elements in flat-panel radiation imaging systems [10]. Kim et al investigated leakage currents and X-ray sensitivity of polycrystalline Cd 1 À x Zn x Te thin films as detectors for digital radiography.…”
Section: Introductionmentioning
confidence: 99%